Feasibility and sustainability of an interactive team-based learning method for medical education during a severe faculty shortage in Zimbabwe - Gray, Jacob (BioMed Central, 2014)
BACKGROUND: In 2010, in the midst of the human immunodeficiency virus (HIV) epidemic in Zimbabwe, 69% of faculty positions in the Department of Medicine of the University of Zimbabwe College of Health Sciences (UZ-CHS) were vacant. To address the ongoing need to train highly skilled HIV clinicians with only a limited number of faculty, we developed and implemented a course for final-year medical students focused on HIV care using team-based learning (TBL) methods. METHODS: A competency-based HIV curriculum was developed and delivered to final-year medical students in 10 TBL sessions as part of a 12 week clinical medicine attachment. A questionnaire was administered to the students after completion of the course to assess their perception of TBL and self-perceived knowledge gained in HIV care. Two cohorts of students completed the survey in separate academic years, 2011 and 2012. Descriptive analysis of survey results was performed. RESULTS: Ninety-six of 120 students (80%) completed surveys. One hundred percent of respondents agreed that TBL was an effective way to learn about HIV and 66% strongly agreed. The majority of respondents agreed that TBL was more stimulating than a lecture course (94%), fostered enthusiasm for the course material (91%), and improved teamwork (96%). Students perceived improvements in knowledge gained across all of the HIV subjects covered, especially in challenging applied clinical topics, such as management of HIV antiretroviral failure (88% with at least a “large improvement”) and HIV-tuberculosis co-infection (80% with at least a “large improvement”). CONCLUSIONS: TBL is feasible as part of medical education in an African setting. TBL is a promising way to teach challenging clinical topics in a stimulating and interactive learning environment in a low-income country setting with a high ratio of students to teachers.